Elective surgery treatment in patient living in rural area with history of recurrent primary spontaneous pneumothorax: A procedure to avoid in absence of pneumothorax. A case report. (2018) - Caterino, Umberto; Di Natale, Davide; Amore, Dario; Scaramuzzi, Roberto; Cicalese, Marcellino; Imitazione, Pasquale; Palma, Albina; Curcio, Carlo
Highlights: Primary Spontaneus Pneumothorax is a common clinical problem. The risk of recurrence is high. The elective surgery treatment in patient with history of recurrent PSP remains questionable. Bleeding or prolonged air leaks represent the most common complications following the lysis of multiple pleural adhesions. We do not recommend the elective surgery treatment in patient living in rural area with recurrent primary spontaneous pneumothorax. Abstract: Introduction: Pneumothorax is defined as accumulation of air in the pleural space with secondary lung collapse resulting in dyspnea or chest pain. Currently the optimal management of spontaneous pneumothorax has been standardized, but the question of elective surgery treatment remains unresolved in patients living in rural area with history of recurrent Primary spontaneous pneumothorax [PSP]. Presentation of case: A 41 years-old white man living in rural area, with a history of recurrent right spontaneous pneumothorax (three subsequent episodes) treated by positioning of chest tube, was admitted to our unit. No respiratory symptoms and normal physical exam were observed on admission although anxiety states was noted. Chest CT scan showed small apical bullae in the right upper lobe without cystic change in the pulmonary parenchyma. Discussion: Recurrence of primary spontaneous pneumothorax represents a complication most frequently occurring within the first year. Among the treatment options, surgical management is needed in 25–50% of all patients suffering from PSP, due to persistent air leak or recurrence. We report the operative complications after elective surgery in a white man living in rural area with a history of recurrent right primary spontaneous pneumothorax. Conclusion: This case report highlights that elective surgery in patients living in rural area with history of recurrence PSP can lead to post-operative complications as bleeding or prolonged air leaks following the lysis of multiple pleural adhesions.